Digitalisasi Dakwah melalui Media Sosial dan Urgensi Logistik Dakwah - Aldi Surizkika1 (Prodi Komunikasi & Penyiaran Islam, Program Pascasarajana, UIN Sunan Gunung Djati Bandung, 2019)
Digital da'wah in the New Media era, such as social media, is a new segment that must be utilized with facts and data on social media user days that have increased significantly every year. This study uses descriptive analysis method with a qualitative research approach through analysis of the literature found in books, journals and other relevant sources. The results showed that the use of social media as a means of preaching has advantages in terms of effectiveness and efficiency than preaching on the pulpit. This can also be optimized with other support such as da'wah logistics which is not important, such as adequate equipment to support today's all-digital da'wah.